Aplikasi Untuk Evaluasi Implementasi Arsitektur Enterprise Menggunakan TOGAF - Beri Noviansyah; Ifaldzi Alwi Hudhori (STMIK Budi Darma, 2022)
The IT Master Plan is a description of the company's strategy for planning the implementation of technology. The advancement of information technology has had a significant impact on organizations, both private and public, because it forces all organizations to compete in the use of information technology to gain a competitive advantage. The implementation of the enterprise architecture has two approaches, namely the enterprise architecture framework and the implementation method of the enterprise architecture. The research method used in this study follows and continues the stages of the Design Science Research Methodology for Information Systems (DSRM). In this research, the analysis carried out is a literature study to determine the model that will be used as an application. In this study, a method of conducting research that refers to the TOGAF method was used. The results of this study are a description of the initial conditions of the research object, so that it can be used as a basis for designing an IT Master Plan based on a Smart Campus. There is a structure for the evaluation method, namely the hybrid evaluation method consisting of initiation, control, and sustainability. The system and interface designs that have been created are implemented to create a fully functional application. The entire structure of this hybrid evaluation method will be assessed on the basis of functionality and effectiveness. This application was made as an implementation of the previous design research. With this design, it can make it easier for practitioners and academics who will evaluate the implementation of enterprise architecture